Early evidence on the XBRL adoption process in Malaysia: drivers and challenges on the technological perspective / Azleen Ilias, Erlane K Ghani and Zubir Azhar - Ilias, Azleen; Ghani, Erlane K; Azhar, Zubir (Faculty of Accountancy, 2019)
This study aims to identify technological factors and how these factors influence XBRL adoption process of the regulators in Malaysia. This paper applied Rogers’s (1983) adoption process and DiPietro, Wiarda and Fleischer’s (1990) Technological, Organisational and Environmental (TOE) framework. The paper adopted a case study approach consisting of interview and document analysis. The data has been analysed with thematic analysis. This paper shows ten (10) factors within the technological perspective. The relative advantage as driving factor while trial ability are the challenging factor in the knowledge and persuasion phase. In the decision-making phase, compatibility of XBRL taxonomy and stability production of XBRL instance documents are the driving factors whilst stability of XBRL taxonomy, standardised XBRL taxonomy, standardised XBRL submission, availability of tools and software and observability are challenges in the XBRL adoption process. In the implementation and confirmation phase, complexity of XBRL taxonomy is considered a challenge in the XBRL adoption process. The findings in this paper serve as strategies to the other regulators that have plans to adopt XBRL as well as to attract the other government agencies to start with XBRL for reporting.